Intertidal and shallow water hydroids from Fiji. 1. Athecata to Sertulariidae - Gibbons, M. J.; Ryland, J. S. (Memoirs of the Queensland Museum, 1989)
Athecate and thecate hydroids, other than hydrocorallines, were collected intertidally and from shallow water around Viti Levu and its nearby islands, Fiji, 1978-1980. The habitats are described. The collected material, other than Plumulariidae (senso lato), is referred to 40 species, which are described and illustrated. Clytia edentula and Sertularia orthogonalis are described as species novae. Some of the remaining species are already known to be widely distributed in the Indo-Pacific, but rarely species include Halecium sibogae Billard, Hydrodendron gardineri (Jarvis) and Diphasia orientalis Billard. The history and status of the generic names Pennaria Oken, Pennaria Goldfuss and Halocordyle Allman are discussed in relation to the 'International Code of Zoological Nomenclature'. It is established that, since Pennaria Oken was disallowed by the International Commission on Zoological Nomenclature in 1956, Pennaria Goldfuss represents a valid introduction and Halocordyle becomes its junior subjective synonym. Sertularia borneensis Billard is retained and not regarded as conspecific with S. turbinata (Lamouroux) but Thyroscyphus vitiensis Marktanner-Turneretscher is referred to T. fruticosus (Esper).Descriptors: CLYTIA EDENTULA new species; SERTULARIA ORTHOGONALIS new species; HALECIUM SIBOGAE; HYDRODENDRON GARDINERI; DIPHASIA ORIENTALIS; PENNARIA; HALOCORDDYLE; SERTULARIA BORNEENSIS; SERTULARIA TURBINATA; THYROSCYPHUS VITIENSIS; THYROSCYPHUS FRUTICOSUSfigs. 1-41.